An ethanol extract of Senduduk fruit (Melastoma malabathricum L) inhibits the expression of vascular endothelial growth factor and tumour necrosis factor alpha in HeLa cells - Deri Edianto; Aznan Lelo; Syafruddin Ilyas; Marline Nainggolan (Medicinski glasnik, 2020)
Aim: Senduduk fruit (Melastoma malabathricum L) is native to Indomalaya and is believed to possess anticancer activity. This study investigated antiangiogenic and anti-inflammation effects of an ethanolic extract of Senduduk fruit (EESF) on HeLa cells. Methods: Cytotoxicity was assayed in HeLa cell cultures exposed to a concentration series of 500-7.8 µg/mL of EESF. IC 50 was determined with a methylthiazol-tetrazolium (MTT) cell viability assay. Antiangiogenic and anti-inflammation activity was evaluated by an immunocytochemical assay of vascular endothelial growth factor (VEGF) and tumour necrosis factor alpha (TNF-?) expression in HeLa cells cultured with 1× or 2× IC 50 or as a control without EESF. Results: IC 50 of the EESF was 956 µg/mL. The intensity of VEGF staining indicated moderate expression in HeLa cells in response to IC 50 , weak expression in response to 2×IC 50 , and strong expression in the absence of the EESF. While the intensity of TNF-? staining indicated moderate expression in HeLa cells in response to IC 50 and to the absence of EESF, and weak expression in response to 2× IC 50. Conclusion: Senduduk fruit extract inhibited VEGF and TNF-? expression in HeLa cells in a concentration-dependent manner.
Keywords: ethanol extract; HeLa cell; Melastoma malabathricum L fruit; TNF-α; VEGF